Silvopastoral systems and their contribution to the environment - Alonso, Jatnel (Cuban Journal of Agricultural Science, 2011)
Some potentialities for the development of technologies were assessed to improve cattle agroecosystems and, at the same time, generate environmental services through the use and adaptation of agricultural practices considering trees and shrubs as indispensable elements in animal production. Different definitions of silvopastoral systems are discussed, as well as their function in the enhancement of pasture production and quality and in the recovery of degraded soils and in the improvement of water resources. Besides, the importance of these systems is analyzed as to the capture of carbon and gases with green house effect and in the conservation of the biodiversity. An analysis of the international experience is performed about the payment of environmental services, as incentive to the use of trees and shrubs in cattle rearing. Key words: capture of carbon, gases with greenhouse effect, biodiversity